The Effect of Audit Tenure, Auditor Switching on Audit Quality in Non-Financial Companies - Erlangga Setyawan; Rita Nurnaningsih; Tri Widyastuti Ningsih; Diah Hari; Dipa Teruna Awaludin (Indonesian Journal Economic Review (IJER), 2026)
This study aims to examine the effect of auditor tenure and auditor turnover on audit quality in non-financial companies listed on the Indonesia Stock Exchange. Audit quality has become a critical issue in maintaining the credibility of financial reports, particularly in the context of an increasingly complex business environment and the rapid development of digital audit technology. Auditor tenure and auditor turnover are structural factors that can influence auditor independence and competence, while digital audit tools represent technological adaptations in audit practice. This study adopted a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The sample consisted of 100 non-financial companies listed on the Indonesia Stock Exchange, selected through purposive sampling. Data were obtained from annual reports and financial statements. The analysis included evaluation of the outer model (convergent validity, discriminant validity, and reliability) and the inner model (path coefficients, R-square, and bootstrapping significance tests). The findings show that auditor tenure significantly influences audit quality in non-financial companies listed on the Indonesia Stock Exchange, indicating that a longer auditor-client relationship improves the auditor's understanding of company characteristics. Auditor turnover also significantly impacts audit quality in non-financial companies listed on the Indonesia Stock Exchange, highlighting the importance of maintaining independence through auditor rotation. This study contributes to the auditing literature by integrating technology variables into audit quality analysis and provides practical implications for auditors and regulators.